2011
DOI: 10.1111/j.1365-2486.2010.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

21st century climate change threatens mountain flora unequally across Europe

Abstract: Continental-scale assessments of 21st century global impacts of climate change on biodiversity have forecasted range contractions for many species. These coarse resolution studies are, however, of limited relevance for projecting risks to biodiversity in mountain systems, where pronounced microclimatic variation could allow species to persist locally, and are ill-suited for assessment of species-specific threat in particular regions. Here, we assess the impacts of climate change on 2632 plant species across al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
408
2
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(444 citation statements)
references
References 64 publications
26
408
2
8
Order By: Relevance
“…However, a species' ability to respond is affected by local geomorphic processes (Macias-Fauria and Johnson 2013), grazing (Speed et al 2012) and community interactions such as dense grassland (Rehm and Feeley 2015). Based on the predicted required shifts, it seems that the species will not be able to track the projected warming which may cause them to lose their potential habitat (Engler et al 2011;Svenning et al 2008) and reduce their population size (Feeley and Silman 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a species' ability to respond is affected by local geomorphic processes (Macias-Fauria and Johnson 2013), grazing (Speed et al 2012) and community interactions such as dense grassland (Rehm and Feeley 2015). Based on the predicted required shifts, it seems that the species will not be able to track the projected warming which may cause them to lose their potential habitat (Engler et al 2011;Svenning et al 2008) and reduce their population size (Feeley and Silman 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, this change was hypothesized to be a response to increases in the abundance of vascular plants. Engler et al (2011) conducted a meta-analysis of the impact of recent climate change on mountain biodiversity and concluded that impacts on florae depend on the relative changes in both temperature and precipitation, with drought having a larger effect than regions where rainfall has been increasing. However, changes in community composition and species diversity also vary with site and microsite characteristics.…”
Section: Community-level Changesmentioning
confidence: 99%
“…A number of recent studies have documented Europewide changes in alpine plant community composition, though there is clear spatial variation in the effects, both regionally and locally (Engler et al 2011;Gottfried et al 2012;Pauli et al 2012;Elumeeva et al 2013). Furthermore, this trend is projected to continue in the future, with stronger impacts in areas where increased temperature coincides with reduced precipitation (Engler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this trend is projected to continue in the future, with stronger impacts in areas where increased temperature coincides with reduced precipitation (Engler et al 2011). Thus, it is of interest to document how different plant communities respond to such environmental changes.…”
Section: Introductionmentioning
confidence: 99%